The relationship between pain catastrophizing, kinesiophobia and subjective knee function during rehabilitation following anterior cruciate ligament reconstruction and meniscectomy: A pilot study - Ana Tichonova; Inesa Rimdeikienė; Daiva Petruševičienė; Eglė Lendraitienė (Medicina, 2016)
Background and objective: Psychological responses to the initial injury and rehabilitation might be an important additional determinant of functional level outcomes after knee surgery. The objectives of this study were (1) to measure pain catastrophizing and kinesiophobia levels and (2) determine their association with self-reported subjective knee function during rehabilitation, following anterior cruciate ligament reconstruction (ACLR) and meniscectomy. Materials and methods: The study involved 41 participants. The levels of catastrophizing (Pain Catastrophizing Scale [PCS]), kinesiophobia (Tampa Scale of Kinesiophobia [TSK-11]), pain (Numeric Pain Rating Scale [NRS]), and subjective knee function (the Knee Injury and Osteoarthritis Outcome Score [KOOS]) were assessed before and after completion of 14-session rehabilitation program. Results: The mean level of catastrophizing changed from 5.8 (SD, 0.9) to 4.2 (SD, 0.5) during rehabilitation (P < 0.05). The mean level of kinesiophobia changed from 22.7 (SD, 0.7) to 18.4 (SD, 0.6) (P < 0.05). There was a moderate negative correlation between the PCS and the KOOS pain, function in daily living, knee-related quality of life subscales before and after rehabilitation (P < 0.05). There was a moderate negative correlation between the TSK-11 score and the KOOS function in daily living subscale before and after rehabilitation (P < 0.05). Conclusions: Pain catastrophizing and kinesiophobia decreased during rehabilitation. A higher pain catastrophizing level correlated with a greater level of knee pain during activities, more difficulties experienced during daily activities before and after rehabilitation. A high level of kinesiophobia correlated with more difficulties experienced in daily activities and poorer knee-related quality of life before and after rehabilitation.